Improving TBI Scores with Effective Morphology-Syntax Teaching Methods in LBB EDU’s 2024 TBI Group Intensive Class - Dika Prestiawan; Hadi Asrori (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This paper underscores the necessity of proper morphology and syntax knowledge, thereby improving grammar mastery in English, before undertaking the Specialist Education Program for Doctors (PPDS). ‘Morphology’ refers to the linguistic branch that studies the internal structures of individual words and how they are formed, whereas ‘syntax’ points to the structures of sentences and how they are formed as phrases, clauses, and sentences. Decent mastery of both aspects will significantly improve the scores in English grammar, thereby considerably improving PPDS participants’ opportunity to obtain high scores and paving the way to better performance in their professional careers. The research involved a final sample of 20 participants, who received targeted grammar instruction over four sessions totaling eight hours. Data were collected through a 50-item grammar composition test designed to measure syntactic and structural understanding. Statistical analysis revealed an increase in the mean score from 53.8 (pretest) to 61.8 (posttest). A paired-sample t-test indicated a significant improvement in students’ performance (t = 2.582, df = 19, p < 0.05, approximate). These results suggest that systematic syntax instruction can enhance learners’ grammatical competence in English. Implications for EFL classroom practice and future pedagogical research are discussed.